PEMAHAMAN KONSEP SISWA PADA MATERI VOLUME PRISMA DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) - Fadlilah, Nur (Mathematics Education Journal, 2025)
Topics prism volume is an important topic to be studied. Study topics prism volume allows students to connect mathematics with an environment that can develop mental abilities and students. In fact, based on the research that has been done before, understanding the concept of students in the material volume of the prism is still lacking. This causes errors occur on problem solving related. Therefore, a series of learning activities designed using learning approach Indonesian Realistic Mathematics Education (PMRI) in accordance with the intended learning in the curriculum in 2013 that find themselves the facts, concepts, and new values are needed in life. This study aimed to investigate the effect of applying the concept pamahaman PMRI against students on the material volume of the prism. In this study, the One-Shot Case Study selected as the type of research that is appropriate to achieve these objectives. The research was conducted in MTs Sakatiga, Indralaya. DOI: https://doi.org/10.22342/jpm.8.2.1864.20-32